Different uptake patterns of 68Ga-FAPI in aseptic loosening and periprosthetic joint infection of hip arthroplasty: A case series and literature review - Wang, Yiqun; Wang, Ruimin; Geng, Lei; Li, Qingxiao; Qi, Erpeng; Shi, Yuanyuan; Wang, Yanmei; Zheng, Qingyuan; Zhang, Guoqiang; Chen, Jiying; Tian, Jiahe (Frontiers in Medicine, 2022)
Background The diagnosis of a periprosthetic joint infection (PJI) is always a difficult point in research on the surgery of joints. The current diagnostic criteria include a comprehensive analysis of multiple tests; however, there are no effective visual examinations yet that can differentiate between aseptic loosening and the PJI. Case presentation This case report describes four patients with symptomatic total hip arthroplasty (THA), two cases of loosening and two cases of infection. Although the four cases were correctly diagnosed by the tissue culture, preoperative tests and pathological examination could not effectively distinguish an infection from a non-infection. Based on a preclinical study and theoretical feasibility, gallium-68 (68Ga)-labeled fibroblast activation protein inhibitor positron emission tomography/computed tomography (68Ga-FAPI PET/CT) was performed. Through 68Ga-FAPI PET/CT scanning, not only were the causes diagnosed correctly but the lesions were also located. Conclusion When the lesion is located between the bone and the prosthesis, 68Ga-FAPI PET/CT could differentiate aseptic loosening from periprosthetic joint infection (PJI). 68Ga-FAPI PET/CT has clear advantages over routine examinations and has a prospective application in detecting PJI.